Zinc Thiocarboxylate Complexes as Precursors for Zinc Sulfide Nanoparticles under Aerobic Conditions. Issue 32 (19th September 2013) - Vallejo‐Sánchez, Daniel; Beobide, Garikoitz; Castillo, Oscar; Lanchas, Mónica
Abstract: Six new compounds with the formula [Zn(SCOR)2 (N–N)] [R = –CH3 (TAc), –C6 H5 (TBn); N–N = 2, 2′‐bipyridine (BPY), 1, 10‐phenanthroline (PHEN), 1, 2‐bis(4‐pyridyl)ethylene (BPE), neocuproine (NEO)] have been obtained by the reaction of Zn(CH3 COO)2 · 2H2 O with the corresponding pyridine derivative and thiocarboxylate in methanol in the ratio Zn/SCOR/N–N = 1:2:1. In all compounds, the metal atom is bonded to sulfur atoms of two thiocarboxylato ligands and to two nitrogen atoms from one pyridine derivative imposing a distorted‐tetrahedral geometry. The use of chelating dipyridine ligands leads to discrete monomeric entities in compounds [Zn(TAc)2 (BPY)] (1 ), [Zn(TBn)2 (BPY)] (2 ), [Zn(TAc)2 (NEO)] (3 ), and [Zn(TBn)2 (PHEN)] (4 ). On the contrary, the bridging capability of the dipyridine BPE ligand gives rise to the polymeric chains observed in compounds [Zn(TAc)2 (μ‐BPE)] (5 ) and [Zn(TBn)2 (μ‐BPE)] (6 ). The occurrence of Zn··· O weak interactions is rationalized on the basis of the νC=O shift and continuous shape measurements. Additionally, the present work demonstrates how ZnS nanoparticles can be obtained by dry thermolysis of the prepared thiocarboxylate complexes under aerobic conditions and moderate temperatures (300 °C). The analysis of the X‐ray diffraction pattern and SEM/TEM images reveals the presence of ZnS crystallites below 10 nm. The influence of the N‐heterocycle and thiocarboxylato ligands on the crystalline phase (blende or wurtzite), size, and purity of the resulting zinc sulfide nanoparticles is discussed. Abstract : Six new air‐stable zinc compounds based on thiocarboxylato ligands all with N‐heterocycles have been synthesized and structurally characterized. Their thermolysis under aerobic conditions and a relatively mild temperature (300 °C) provides blende and wurtzite ZnS nanoparticles with crystallite diameters below 10 nm.